2007
DOI: 10.1159/000112954
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Serum Concentrations in Healthy Volunteers Are Associated with Depression-Related Personality Traits

Abstract: Background: Alterations of the hypothalamic-pituitary-thyroid system at the hypophyseal level have been described in affective disorders. The NEO Five-Factor Inventory is a widely used instrument, which assesses neuroticism, a strong marker for vulnerability to depression. Methods: Endogenous serum concentrations of thyroid-stimulating hormone (TSH), free T3 and free T4 were measured and the NEO Five-Factor Inventory was performed in 121 healthy unrelated volunteers (51 male, 70 female; median age: 23 years, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In accordance with our results, Forman et al (15) found no association between lifetime diagnosis of depression and thyroid function. Frey et al (46) found that low TSH levels in 121 healthy subjects were associated with neuroticism. Perhaps, the differences in results can be explained by the differences in study populations.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, Forman et al (15) found no association between lifetime diagnosis of depression and thyroid function. Frey et al (46) found that low TSH levels in 121 healthy subjects were associated with neuroticism. Perhaps, the differences in results can be explained by the differences in study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical depression occurs in more than 40% of people suffering from hypothyroidism [50,51]. Indeed, low TSH levels in healthy individuals might be linked to an increased risk of depression [52]. Vice versa, patients suffering from depression display higher than expected rates of subclinical hypothyroidism.…”
Section: Depression As An Endocrine Disordermentioning
confidence: 99%
“…tyrosine is present in high concentrations in many fishes (160% in tuna when compared with chicken) [118,119]. Tyrosine is a biological precursor of dopamine, norepinephrine, and epinephrine, a component of thyroxine and triiodothyronine (hypothyreosis is common in 30% of depressive patients) and its deficiency has been implicated in depression [119][120][121][122].…”
Section: Special Nutritional Compounds Which Could Influence Depressimentioning
confidence: 99%